2016
DOI: 10.7880/abas.0160803a
|View full text |Cite
|
Sign up to set email alerts
|

Spurious Correlation between Work Environment and Job Satisfaction

Abstract: This study conducted a questionnaire survey of all employees at a company that moved its office location, both before and after the move. Results of the survey showed that while work environment satisfaction rose significantly because of the office move, there was no significant change in job satisfaction (in fact, some deterioration was observed). In addition, there was no significant change in the perspective index, which is regarded as a factor in job satisfaction, after the move. Existing studies on office… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
0
5
0
7
Order By: Relevance
“…Hypothesis 6: There is a positive impact of benefits on job satisfaction. Work environment: (Pearson, (1991) and ;Inamizu, (2016) identified that organizational values and physical conditions are factors related to the work environment. The physical working conditions refer to "the quantity of work and availability of resources such as machines and tools, ventilation, lighting, workspace and air conditioning" Oosthuizen (2001).…”
Section: Job Satisfaction and Antecedent Factorsmentioning
confidence: 99%
“…Hypothesis 6: There is a positive impact of benefits on job satisfaction. Work environment: (Pearson, (1991) and ;Inamizu, (2016) identified that organizational values and physical conditions are factors related to the work environment. The physical working conditions refer to "the quantity of work and availability of resources such as machines and tools, ventilation, lighting, workspace and air conditioning" Oosthuizen (2001).…”
Section: Job Satisfaction and Antecedent Factorsmentioning
confidence: 99%
“…The office environment has become a popular topic in recent years. In particular, more research is being done on the relationship between employees' activities and communication in nonterritorial offices and activity-based working/offices (Inamizu, 2013(Inamizu, , 2014(Inamizu, , 2015(Inamizu, , 2016Inamizu & Makishima, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In such a case, the supplier can have a higher profitability as incentives since the volume will be lower than if the parts were standardized. 7 There are insightful studies, Inamizu (2016) and Takahashi, Ohkawa, and Inamizu (2014), that note spurious correlations on existing research.…”
Section: Re-examination: Regression Analysismentioning
confidence: 99%